Metabolic syndrome and metabolic abnormalities in patients with major depressive disorder: a meta-analysis of prevalences and moderating variables. Issue 10 (21st November 2013) - Vancampfort, D.; Correll, C. U.; Wampers, M.; Sienaert, P.; Mitchell, A. J.; De Herdt, A.; Probst, M.; Scheewe, T. W.; De Hert, M.
Abstract : Background: Individuals with depression have an elevated risk of cardiovascular disease (CVD) and metabolic syndrome (MetS) is an important risk factor for CVD. We aimed to clarify the prevalence and correlates of MetS in persons with robustly defined major depressive disorder (MDD). Method: We searched Medline, PsycINFO, EMBASE and CINAHL up until June 2013 for studies reporting MetS prevalences in individuals with MDD. Medical subject headings 'metabolic' OR 'diabetes' or 'cardiovascular' or 'blood pressure' or 'glucose' or 'lipid' AND 'depression' OR 'depressive' were used in the title, abstract or index term fields. Manual searches were conducted using reference lists from identified articles. Results: The initial electronic database search resulted in 91 valid hits. From candidate publications following exclusions, our search generated 18 studies with interview-defined depression ( n  = 5531, 38.9% male, mean age = 45.5 years). The overall proportion with MetS was 30.5% [95% confidence interval (CI) 26.3–35.1] using any standardized MetS criteria. Compared with age- and gender-matched control groups, individuals with MDD had a higher MetS prevalence [odds ratio (OR) 1.54, 95% CI 1.21–1.97, p  = 0.001]. They also had a higher risk for hyperglycemia (OR 1.33, 95% CI 1.03–1.73, p  = 0.03) and hypertriglyceridemia (OR 1.17, 95% CI 1.04–1.30, p  = 0.008). Antipsychotic use ( p  < 0.05) significantly explained higher MetS prevalence estimates in MDD. Differences in MetS prevalences were not moderated by age, gender, geographical area, smoking, antidepressant use, presence of psychiatric co-morbidity, and median year of data collection. Conclusions: The present findings strongly indicate that persons with MDD are a high-risk group for MetS and related cardiovascular morbidity and mortality. MetS risk may be highest in those prescribed antipsychotics.